The local socioeconomic effects of gold mining: Evidence from Ghana. Issue 4 (November 2019) - Benshaul-Tolonen, Anja; Chuhan-Pole, Punam; Dabalen, Andrew; Kotsadam, Andreas; Sanoh, Aly
Abstract: Ghana is experiencing its third gold rush, and this paper sheds light on the socioeconomic impacts of this rapid expansion in industrial production. Using a rich dataset consisting of geocoded household data combined with detailed information on gold mining activities, we conduct two types of difference-in-differences estimations that provide complementary evidence. The first is a local-level analysis that identifies an economic footprint area very close to a mine, and the second is a district-level analysis that captures the fiscal channel. The results indicate that men are more likely to benefit from direct employment as miners compared to men further away, and that women in mining communities may more likely gain from indirect employment opportunities and earn cash for work. We also find that infant mortality rates decrease significantly in mining communities, compared to the evolution in communities further away.